A Need for More Molecular Profiling in Brain Metastases - Shen, Erica; Van Swearingen, Amanda E. D.; Price, Meghan J.; Bulsara, Ketan; Verhaak, Roeland G. W.; Baëta, César; Painter, Brice D.; Reitman, Zachary J.; Salama, April K. S.; Clarke, Jeffrey M.; Anders, Carey K.; Fecci, Peter E.; et al. (Frontiers in Oncology, 2022)
As local disease control improves, the public health impact of brain metastases (BrM) continues to grow. Molecular features are frequently different between primary and metastatic tumors as a result of clonal evolution during neoplasm migration, selective pressures imposed by systemic treatments, and differences in the local microenvironment. However, biomarker information in BrM is not routinely obtained despite emerging evidence of its clinical value. We review evidence of discordance in clinically actionable biomarkers between primary tumors, extracranial metastases, and BrM. Although BrM biopsy/resection imposes clinical risks, these risks must be weighed against the potential benefits of assessing biomarkers in BrM. First, new treatment targets unique to a patient’s BrM may be identified. Second, as BrM may occur late in a patient’s disease course, resistance to initial targeted therapies and/or loss of previously identified biomarkers can occur by the time of occult BrM, rendering initial and other targeted therapies ineffective. Thus, current biomarker data can inform real-time treatment options. Third, biomarker information in BrM may provide useful prognostic information for patients. Appreciating the importance of biomarker analyses in BrM tissue, including how it may identify specific drivers of BrM, is critical for the development of more effective treatment strategies to improve outcomes for this growing patient population.